1983
DOI: 10.1891/0047-2220.14.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Licensure, Confidentiality, and Privileged Communication: Implications for Private Practice in Rehabilitation

Abstract: This article addresses the importance of confidentiality and privileged communication in the counselor-client relationship. State licensure statutes are reviewed in regard to their confidentiality and/or privileged. communication provisions. The implications of legal confidentiality and privileged communication on the private-for-profit practice of rehabilitation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Matkin stated that "failure to ensure the client's privacy couldresult in charges of breach of privacy, breach of contract, defamation, or malpractice (negligence)" (p. 209). Cottone, Pullen, and Wilson (1983) concluded that legal confidentiality and privileged communication provisions in professional counselor licensure statutes would help to ensure that rehabilitation counselors would not be placed in a position of conflicting loyalties. Legal confidentiality would act to protect a client's privacy, and privileged communication would help to prevent testimony on a client's case without client permission.…”
Section: The Issuesmentioning
confidence: 99%
“…Matkin stated that "failure to ensure the client's privacy couldresult in charges of breach of privacy, breach of contract, defamation, or malpractice (negligence)" (p. 209). Cottone, Pullen, and Wilson (1983) concluded that legal confidentiality and privileged communication provisions in professional counselor licensure statutes would help to ensure that rehabilitation counselors would not be placed in a position of conflicting loyalties. Legal confidentiality would act to protect a client's privacy, and privileged communication would help to prevent testimony on a client's case without client permission.…”
Section: The Issuesmentioning
confidence: 99%